Business Activity Management for Service Networks in Cloud Environments - Janiesch, Christian; Fischer, Robin; Matzner, Martin; Müller, Oliver (Proceedings of the 6th Workshop on Middleware for Service-oriented Computing (MW4SOC 2011), 2011)
Companies struggle to find ways to manage intra- and inter-organizational service networks communicating in a distributed fashion across the globe. We review the state-of-the-art of managing choreographed service networks and put it in relation to process analytics and complex event processing (CEP) against the background of Cloud computing. We present an initial architecture for Event-driven Business Activity Management of service networks which also takes into consideration levels of virtualization. The architecture can serve as a blueprint for flexible business activity monitoring applications as well as closed loop service choreography control solutions. We illustrate the interaction of Cloud infrastructure, services networks, and CEP systems with a number of use cases. In addition, we discuss future research directions based on our experiences from early prototype